Nationalism before the nation state : literary constructions of inclusion, exclusion, and self-definition (1756-1871) - Paulus, Dagmar; Pilsworth, Ellen (National cultivation of culture ;, 2020)
"Though the German Nation State was only founded in 1871, the German nation had been imagined long before it ever took political shape. Covering the period from the Seven Years' War to the foundation of the German nation, Nationalism before the Nation State: Literary Constructions of Inclusion, Exclusion, and Self-Definition (1756-1871) explores how the nation was imagined by different groups, at different times, and in connection with other ideologies. Between them the eight chapters in this volume explore the connections between religion, nationalism and patriotism, and individual chapters show how marginalised voices such as women and Jews contributed to discourses on national identity. Finally, the chapters also consider the role of memory in constructing ideas of nationhood. Contributors are: Johannes Birgfeld, Anita Bunyan, Dirk Göttsche, Caroline Mannweiler, Alex Marshall, Dagmar Paulus, Ellen Pilsworth, and Ernest Schonfield"--